2007
DOI: 10.1097/01.ans.0000286619.31398.fc
|View full text |Cite
|
Sign up to set email alerts
|

Relational Practice and Nursing Obligations

Abstract: Nursing relationships and the enactment of nursing values and goals in contemporary healthcare contexts are becoming increasingly challenging. Using a relational inquiry lens, the authors examine the interface of relationships, ethics, and effective nursing practice and the way in which personal and contextual elements continuously influence and shape nursing relationships in many ways. The nursing obligations underpinning relational practice are examined, and the way in which relational inquiry can enhance nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 27 publications
1
107
0
9
Order By: Relevance
“…We would add that they are reflective of a political economy that is based on neo-liberal values that underpin shifts to more business focused and efficiency models of health care. Repeatedly we have seen in our own work how challenges to ethical nursing practice and increased moral distress are shaped by a neo-liberal socio-political contexts (Doane et al 2009;Doane and Varcoe 2007;Rodney and Varcoe 2001;Storch et al 2002Storch et al , 2009Varcoe et al 2003Varcoe et al , 2004. Different approaches to, and rates of health care reform, a global phenomenon with varied features internationally, have led to different rates of liberalization.…”
Section: Contextual Tensionsmentioning
confidence: 96%
“…We would add that they are reflective of a political economy that is based on neo-liberal values that underpin shifts to more business focused and efficiency models of health care. Repeatedly we have seen in our own work how challenges to ethical nursing practice and increased moral distress are shaped by a neo-liberal socio-political contexts (Doane et al 2009;Doane and Varcoe 2007;Rodney and Varcoe 2001;Storch et al 2002Storch et al , 2009Varcoe et al 2003Varcoe et al , 2004. Different approaches to, and rates of health care reform, a global phenomenon with varied features internationally, have led to different rates of liberalization.…”
Section: Contextual Tensionsmentioning
confidence: 96%
“…These relationships were characterized by tension, ambiguity, power struggles, and an ongoing process of negotiating assumptions about "private" and "public" caregiving as home care nurses tried to delegate care to family caregivers-although less so in palliative situations (Ward-Griffin, 2001;Ward-Griffin & McKeever, 2000). Although there is increasing conceptual recognition given to partnerships with family caregivers (Harvath et al, 1994;Keating, Fast, Connidis, Penning, & Keefe, 1997), research such as the above revealed that relationships between family and professional caregivers might not be as reflective of true partnerships, or indeed, true "relational practice" (Hartrick Doane & Varcoe, 2007;Parker, 2002) as we would like them to be.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…71 The result is a further opening of a space for the expression of another's fear, uncertainty, and vulnerability. 72 The nurse in Edson's 66 play penetrates the patient's intellectual exterior (Vivian Bearing is a scholar of English literature) to 'comfort the terrified woman hiding underneath -without which the play would be an exercise in despair' (p.9). 73 The scene is a powerful illustration of non-abandonment and a model case of compassion in nursing.…”
Section: Relational Knowingmentioning
confidence: 99%